Today you die - FauntLeRoy, Don.; Seagal, Steven; Treach, 1970-; Millennium Films; Luminocity; Equity Pictures, Inc.; Sony Pictures Home Entertainment (Firm) (Culver City, Calif. : Sony Pictures Home Entertainment, 2005)
A high-tech thief's latest job goes wrong and he finds himself behind bars. While there, he has a supernatural experience that changes his life forever.
Title from container.
Director of photography, Don E. Fauntleroy ; editor, Robert Ferretti ; music, Steve Edwards.
Steven Seagal, Treach.
MPAA rating: R; for strong violence and pervasive language.
VHS
Closed-captioned.
Keywords: Thieves -- Nevada -- Las Vegas -- Drama; Escapesz Nevada -- Nevada -- Las Vegas -- Drama; Revenge -- Drama; Feature films; Video recordings for the hearing impaired